DEVELOPING PROJECT BASED LEARNING ACTIVITIES IN ENGLISH CLASSES FOR IMPLEMENTING MERDEKA CURRICULUM IN SMPN 2 SINGARAJA - Darmawan, Cahya Swaztine; Padmadewi, Ni Nyoman; Utami, IGA. Lokita Purnamika (Undiksha Press, 2024)
This study aims to develop project-based learning activities in English classes for implementing the Merdeka curriculum in the 7th grade second semester. This study has an objective purpose. First to describe the specification of PJBL activities needed, second to describe the kinds of PJBL activities that result from its specification, and last, to analyze the quality of the development result. At the end, this study resulted in the book module with PJBL design. ADDIE from Kurt (2018) was used as a model in developing the book. The book was designed based on needs analysis obtained from teacher-student questionnaires, interviews, and document analysis. The results of the needs analysis provided PJBL activity specifications that emphasize the relevance of PJBL activities to the syllabus, as well as student characteristics, Pancasila Student Profile emphasis, and 6C (communication skills, collaboration, creativity, critical thinking, computational thinking, and compassion skills). The eight steps of implementing PjBL by Hamidah (2020) were used to develop this book. Therefore, two kinds of books' modules are developed by the researcher: a teacher’s book and a student's book. And the last is product quality test results; it showed that the PJBL Activity Book has amazing quality materials in the aspects of content, language, and media. With the Greogory’s Result 1.00 it means very good quality. Therefore, this study provided references regarding PJBL activities in book form for teachers to use in English learning and also for the students to learn English material.